Study of ATP/GTP binding protein -1 (AGTPBP-1) in Fibrotic Lung Disease with and without COVID-19 Vaccination - Raed Mahmoud Al-Azawee; Zeinab M. Al-Rubaei (Iraqi Journal of Pharmaceutical Sciences, 2025)
Background : It took less than two months for the severe acute respiratory syndrome that caused by coronavirus disease 2019 to become a palsoemic . ATP/GTP binding protein 1 (AGTPBP1) is responsible for encoding a number of proteins, including cytosolic carboxypeptidase1 (CCP1), which has been investigated in degenerative diseases also has a role in the regulation of polyglutamylation of tubulin. Patients and methods : A 150 people participated in this study were split into three groups, The first group (G1), served as control group included (50) subjects . Second group (G2) consisted of (50) Fibrotic Lung Disease (FLD) patients without COVD-19 vaccine . Third group (G3) consisted of (50) FLD patients with COVID-19 vaccine . ESR , CRP,LDH, Ferritin ,D-dimer. were measured by enzymatic method . AGTPBP1 levels were measured using the ELISA technique . Results : Result show highly significant increases in ESR, CRP and LDH levels among three groups . ANOVA descriptive analysis of Ferritin, D-dimers and AGTPBP1 for all studied groups . Show a significant increase in levels of G3 and G2 comparing to G1 . In addition a significant increase found in G3 comparing to G2 . Conclusion : The present study submits novelty in COVID-19 fields by Focus on role of new parameter such as AGTPBP1 in corona-19 vaccine (Pfizer) that used in Iraq .